Comparative Evaluation of Crithmum maritimum and Origanum dictamnus Cultivation on an Extensive Urban Green Roof - Aikaterini N. Martini; Maria Papafotiou (Land)
Considering that urban horticulture benefits from green roof technology, the effects of substrate type (compost-perlite-pumice 3:3:4, v/v and compost-perlite-pumice-soil 3:3:2:2, v/v) and depth (7.5 cm and 15 cm) were comparatively evaluated in the cultivation of Crithmum maritimum and Origanum dictamnus on an urban green roof in modules that included a green roof infrastructure layering. During the first cultivation period (December 2015–August 2016), plants of C. maritimum were taller and had greater diameter than those of O. dictamnus. Greater fresh and dry weights of all plant parts were observed in C. maritimum, as well as in the deep substrates compared to the shallow ones. During the second cultivation period (September 2016–August 2017), the growth of O. dictamnus surpassed that of C. maritimum, while plant height and foliage diameter, as well as the fresh and dry weight of all plant parts were greater in the deep substrates for both species. Conclusively, both species grew satisfactorily on an extensive urban Mediterranean green roof, while the deep substrate favored all their growth parameters. O. dictamnus responded better in the soil-containing substrate regarding survival, growth, and flowering, as opposed to C. maritimum that showed equal response in both substrate types.